Analisis Peran Leasing Berbasis Syariah Terhadap Peningkatan Akses Pembiayaan Pada Perdagangan Internasional - Desta Marta nita; Ahmad Habibi; Muhammad Iqbal Fasa (Advances In Education Journal, 2025)
This study aims to analyze the role of Sharia-based leasing in increasing access to financing in the international trade sector. International trade plays a crucial role in expanding markets and strengthening global economic growth. Conventional interest-based financing systems often create economic inequality and are inconsistent with the principles of justice in Islam. Therefore, Sharia-based leasing, or Ijarah and Muntahiyah Bittamlik (IMBT), has emerged as an alternative solution capable of providing financing for productive assets without riba (riba), gharar (gharar), and maisir (gambling). The research method used is a qualitative approach using library research techniques, which examines various literature, fatwas (religious rulings), and previous empirical research findings. The results show that Sharia-based leasing plays a significant role in expanding financial inclusion, facilitating business actors in acquiring assets for export and import, and supporting the stability of cross-border transactions through the principles of fairness and contractual transparency. Furthermore, the implementation of Sharia-based leasing promotes economic efficiency and the sustainability of international trade by prioritizing the principles of partnership and risk sharing. Thus, Sharia-based leasing serves not only as a financing instrument but also as a means of empowering the global economy based on the values ​​of maqasid al-Shari'ah.